A bioequivalence comparison of two formulations of rifampicin (300- vs 150-mg capsules): An open-label, randomized, two-treatment, two-way crossover study in healthy volunteers - Chik, Zamri; Basu, Roma Choudhury; Pendek, Rokiah; Lee, Toong Chow; Mohamed, Zahurin (Elsevier, 2010)
Background: Rifampicin is a semisynthetic antibiotic derivative of rifamycin used worldwide for the treatment of various forms of tuberculosis. Objective: The objective of this study was to compare, under fasting conditions in healthy volunteers, the rate and extent of absorption of a generic rifampicin capsule in oral dosage form versus the proprietary equivalent formulation for the purpose of registration approval of the test formulation. Methods: This was an open-label, randomized, 2-treatment, 2-way crossover study with an 8-week washout period between the 2 study arms. Healthy volunteers received a 300-mg capsule of the test formulation (Idaman Pharma Manufacturing Sdn. Bhd.) or two 150-mg capsules of the reference formulation. Blood samples were collected predose and at 45 minutes and 1.25, 1.5, 2, 2.25, 2.5, 3, 3.5, 4, 6, 8, 10, 12, and 24 hours postdose. Plasma concentrations of rifampicin and its metabolite, 25-desacetyl rifampicin, were analyzed using a validated HPLC method. The formulations were considered bioequivalent if the 90 CIs for C(max) and AUC were within the predetermined bioequivalence range (80-125, according to the guidelines of the US Food and Drug Administration, or 75-133 for C(max) only, as set by the European Commission European Medicines Agency and the National Pharmaceutical Control Bureau of Malaysia). Tolerability was assessed by verbally questioning subjects regarding their well-being and any feelings of discomfort. All events reported by the subjects (serious or mild) were recorded on adverse-event forms. Results: Fourteen healthy subjects (10 males, 4 females) with a mean age of 22.6 years (range, 20-28 years) and a mean body mass index of 22.2 kg/m(2) (range, 18.3-29.9 kg/m(2)) were enrolled in the study; all 14 completed the trial as outlined in the protocol. The mean values for C(max), T(max), AUC(0-24), and AUC(0-infinity) with the test formulation of rifampicin were 7.20 mu g/mL, 1.32 hours, 37.12 mu g/mL . h, and 39.69 mu g/mL . h, respectively; for the reference formulation, the values were 7.65 mu g/mL, 1.71 hours, 38.92 mu g/mL . h, and 42.24 mu g/mL . h. For 25-desacetyl rifampicin, the mean values for C(max), T(max), AUC(0-24), and AUC(0-infinity) with the test formulation were 0.63 mu g/mL, 3.45 hours, 4.92 mu g/mL . h, and 6.27 mu g/mL . h; for the reference formulation, the values were 0.7 mu g/mL, 3.27 hours, 5.23 mu g/mL . h, and 6.84 mu g/mL . h. For rifampicin, the 90 CIs for the test formulation/reference formulation ratio for the logarithmic transformations of both C(max) and AUC(0-infinity). were within the bioequivalence limit of 80 to 125 (80.9-109.7 and 80.7-103.2, respectively). For 25-desacetyl rifampicin, the 90 CI for the test formulation/reference formulation ratio for the logarithmic transformations of AUC(0-24) (80.0-104.7) was within the bioequivalence limit of 80 to 125. However, the 90 CI for C(max) (78.4-102.2) was outside this limit but still within the acceptance limit for C(max) when adhering to the bioequivalence range of 75 to 133. No adverse events were reported during the study. Conclusions: This study found that the 300-mg test capsule and the 150-mg reference capsules of rifampicin met the regulatory criteria for assuming bioequivalence in these fasting healthy volunteers. Both formulations appeared to be well tolerated in the population studied. (Clin Ther. 2010;32:1822-1831) (C) 2010 Excerpta Medica Inc.